Multivariate analysis and vigor tests to determine the quality of Brachiaria decumbens seeds - Silva, Givanildo; Martins, Cibele; Bruno, Riselane; Pereira, Francisco Elder; Jeromini, Tatiane (Revista Ciência Agronômica, 2019)
This study aimed to verify the efficiency of multivariate analysis in the identification of promising vigor tests for the evaluation of the physiological quality of seed lots of Brachiaria decumbens cv. Basilisk. Seeds of B. decumbens cv. Basilisk were tested for the following parameters: water content, germination, first germination count, cold test, electrical conductivity, seedling growth, seedling dry mass, first count and emergence percentage of seedlings in laboratory substrate, and seedling emergence in the field. The data obtained in each test—all completely randomized experimental designs—were analyzed separately by means of analysis of variance, Scott-Knott’s test, and multivariate analysis. Principal component analysis is efficient to discriminate vigor and seed germination tests capable of identifying the top performance batch in the field. Germination, first germination count, emergence of seedlings in sand, first seedling emergence count in sand, shoot length, and the cold test are promising in the evaluation of the physiological quality of seed lots of B. decumbens cv. Basilisk, providing similar information to that from the emergence of field seedlings.